Bioceramic composites for orthopaedic applications: A comprehensive review of mechanical, biological, and microstructural properties. Issue 3 (1st February 2021) - Shekhawat, Deepika; Singh, Amit; Banerjee, M.K.; Singh, Tej; Patnaik, Amar
Abstract: Bioceramics have been widely utilized for orthopaedic applications in which the biocompatibility and mechanical properties of the materials are vital characteristics to be considered for their clinical use. Till date, extensive studies have been devoted to developing a range of scientific ways for tailoring the microstructure of bioceramics in order to attain the trade-off of mechanical properties and biocompatibility of the final product. Owing to low reactivity, earlier stabilization and longer functional life of bioceramic, the developed implants are capable of replicating the mechanical behaviour of original bone. As the safety of the patient and its ultimate functionality are the ultimate goal of the selected implant material hence, the present literature survey investigates and brings forth the important aspects associated to the mechanical, biological and microstructural characteristics of bioceramics employed in orthopaedic applications. The review paper majorly focuses on effective utilization of various materials as an additive in bioceramics and processing techniques used for enhancement of properties, enabling the use of material in orthopaedic applications. The influence of various additives on the microstructure, mechanical properties and biological performance of developed bioceramics orthopaedic implants has been elaborately discussed. Furthermore, future prospects are proposed to promote further innovations in bioceramics research.